Justinian und die Armee des frühen Byzanz - Koehn, Clemens (Millennium-Studien / Millennium Studies, 2018)
Although the long reign of Emperor Justinian I (527-565 CE) and the military history of late antiquity have been frequent subjects of ancient historical research, the emperor's military policy has not been closely studied until now. This study contributes to our understanding the specific course of decision-making and the intentions of imperial activity in the military sector.